2012
DOI: 10.1016/j.fm.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a consensus method for culture of Clostridium difficile from meat and its use in a survey of U.S. retail meats

Abstract: Three previously described methods for culture of Clostridium difficile from meats were evaluated by microbiologists with experience in C. difficile culture and identification. A consensus protocol using BHI broth enrichment followed by ethanol shock and plating to selective and non-selective media was selected for use, and all participating laboratories received hands-on training in the use of this method prior to study initiation. Retail meat products (N = 1755) were cultured for C. difficile over 12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…Recently, Limbago et al (2012) developed a consensus method for culture of CD from 18 (2) 0 (0) 0 (0) 0 (0) meat and then used the method for doing a survey of US retail meats. They examined 1755 retail meat (fresh, nonfrozen ground beef and turkey, whole pork chops and chicken breasts) samples over 12 months during 2010-2011 from 9 FoodNet sites.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Limbago et al (2012) developed a consensus method for culture of CD from 18 (2) 0 (0) 0 (0) 0 (0) meat and then used the method for doing a survey of US retail meats. They examined 1755 retail meat (fresh, nonfrozen ground beef and turkey, whole pork chops and chicken breasts) samples over 12 months during 2010-2011 from 9 FoodNet sites.…”
Section: Discussionmentioning
confidence: 99%
“…While C. difficile has been isolated from food, food-borne transmission of disease has not been demonstrated, even though the predominant strain types isolated in food are ribotypes 027 and 078, strains well established to cause human disease (197)(198)(199)(200)(201). One recent study reported C. difficile recovery from 5 out of 119 seafood and fish samples from a grocery store (all of which were of ribotype 078) (200); in contrast, a large survey that tested for C. difficile in 1,755 retail meat samples from across the United States (ground beef, ground turkey, chicken breast, and pork chop) found that no C. difficile was isolated from any of these specimens (198), which suggests a low prevalence of contaminated meat products. Thus, the true impact of food as a vehicle for C. difficile transmission remains to be clarified.…”
Section: Evolving Epidemiology Clinical Implications Of Strain Typingmentioning
confidence: 99%
“…This is consistent with an earlier study on the epidemiology of C. perfringens (Shandera et al, 1983) and is not surprising because the organism is common in animals and ubiquitous in the environment (Labbe and Juneja, 2006) and because C. perfringens grows readily under pH conditions between 6.0 and 7.0, a range similar to that of most meat and poultry products (Labbe and Juneja, 2006). C. perfringens type A, including isolates producing the cpe enterotoxin associated with human disease, has also been isolated from raw meat and poultry at retail (Wen and McClane, 2004;Limbago et al, 2012) and in food service establishments (Bryan and McKinley, 1979). Contamination of meats and other foods has been documented to occur through contact of carcasses with feces as well as via cross-contamination by other foods or contaminated surfaces during food processing or preparation (Juneja et al, 2010).…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%